2016
DOI: 10.1542/peds.2016-2146
|View full text |Cite
|
Sign up to set email alerts
|

Countering Vaccine Hesitancy

Abstract: Immunizations have led to a significant decrease in rates of vaccine-preventable diseases and have made a significant impact on the health of children. However, some parents express concerns about vaccine safety and the necessity of vaccines. The concerns of parents range from hesitancy about some immunizations to refusal of all vaccines. This clinical report provides information about addressing parental concerns about vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
167
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(178 citation statements)
references
References 71 publications
5
167
1
5
Order By: Relevance
“…This study is important since it demonstrated an increase in parental knowledge and satisfaction with the provider after two sessions of VEE but not in parental perception of immunization effectiveness and comfort with immunization decision making. Since vaccine hesitancy develops from complex cultural and psycho‐social influences (Edwards, Hackell, The Committee on Infectious Diseases, & The Committee on Practice and Ambulatory Medicine, ), additional VEE sessions or community approaches may be needed to increase perception of immunization effectiveness and comfort in decision making in parents of young children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study is important since it demonstrated an increase in parental knowledge and satisfaction with the provider after two sessions of VEE but not in parental perception of immunization effectiveness and comfort with immunization decision making. Since vaccine hesitancy develops from complex cultural and psycho‐social influences (Edwards, Hackell, The Committee on Infectious Diseases, & The Committee on Practice and Ambulatory Medicine, ), additional VEE sessions or community approaches may be needed to increase perception of immunization effectiveness and comfort in decision making in parents of young children.…”
Section: Discussionsupporting
confidence: 90%
“…Parental concerns must be discussed. Stories, personal examples, and anecdotes are more convincing than reciting disease numbers (Edwards et al., ). Physicians were more successful with undecided parents when they used personal experiences such as their own children/grandchildren being immunized (Kempe et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In USA, California recently passed legislation, joining Mississippi and West Virginia, in eliminating all but medical exemptions for school entry . The American Academy of Pediatrics released a policy statement in August to support the elimination of all non‐medical exemptions and have given more explicit support to paediatricians who wish to dismiss vaccine‐rejecting parents from their practice . By contrast, the Royal Australasian College of Physicians do not support the removal of non‐medical exemptions and explicitly discourage dismissing unvaccinated children from paediatric practices …”
Section: Introductionmentioning
confidence: 99%
“…7 The American Academy of Pediatrics released a policy statement in August to support the elimination of all nonmedical exemptions and have given more explicit support to paediatricians who wish to dismiss vaccine-rejecting parents from their practice. 8,9 By contrast, the Royal Australasian College of Physicians do not support the removal of non-medical exemptions and explicitly discourage dismissing unvaccinated children from paediatric practices. 10 However, the Australian government has removed nonmedical exemptions, previously in place for parents who actively declined vaccination for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Patient Protection and Affordable Care Act of 2010 eliminated cost sharing in the form of copays, coinsurance, or deductibles for vaccines recommended by the ACIP . In addition to reducing financial barriers, studies have been done to better understand parental concerns about childhood immunizations and reasons for vaccine hesitancy, resulting in guidance for health care providers to enhance parental communication …”
Section: Immunization Requirements and Parental Concernsmentioning
confidence: 99%